2018
DOI: 10.1159/000487474
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Epithelial Hyperplasia after 5-Fluorouracil Injection

Abstract: Background: 5-Fluorouracil (5-FU) is a pyrimidine analogue which selectively inhibits DNA synthesis, RNA synthesis, and VEGF antibodies. 5-FU is widely used in ophthalmology for inhibition of postoperative corneal scarring and scleral bleb fibrosis. Case Presentation: In this case report, we describe an unusual case of a 65-year-old male who presented to the clinic with progressive decrease of vision after he underwent a revision of scleral bleb with the administration of 0.05 mL 5-FU (2.5 mg) injection and wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 7 publications
0
5
1
1
Order By: Relevance
“…Topical immunotherapy or chemotherapy is best avoided, considering that 5FU itself can trigger epithelial hyperplasia and interferon-α2b has shown no benefit. [ 5 10 ] Despite the fact that purported predisposing factors can continue to exist after surgical management, no recurrences were noted in any case in the present series. Fibrosis resulting from surgical intervention may have a role to play in interrupting the interplay of epithelial and stromal reactive changes.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Topical immunotherapy or chemotherapy is best avoided, considering that 5FU itself can trigger epithelial hyperplasia and interferon-α2b has shown no benefit. [ 5 10 ] Despite the fact that purported predisposing factors can continue to exist after surgical management, no recurrences were noted in any case in the present series. Fibrosis resulting from surgical intervention may have a role to play in interrupting the interplay of epithelial and stromal reactive changes.…”
Section: Discussionmentioning
confidence: 53%
“…Known causes of corneal epithelial hyperplasia include refractive procedures that involve stromal ablation and drugs such as 5-fluorouracil (5FU). [ 9 10 ] Interestingly, none of the patients in this series had any form of iatrogenic or accidental trauma that could have initiated the reactive process. However, a consistent feature was the presence of subepithelial thickening on ASOCT and corresponding chronic inflammatory infiltrate and solar elastosis on histopathology.…”
Section: Discussionmentioning
confidence: 95%
“…In a case study of 52 patients, canicular stenosis was found in 5.8% of patients and epiphora in 26.9% of patients [ 30 ]. Bukhari et al describes a case where a patient was treated corneal epithelial hyperplasia with cyclosporine 1% [ 31 ]. Raina et al was able to effectively treat loss of vision on the right eye via intravenous administration of 1 g of methylprednisolone for five days [ 32 ].…”
Section: Chemotherapymentioning
confidence: 99%
“…Além disso, foram relatados casos de conjuntivite e formação excessiva de lágrimas (estenose do ducto lacrimal -fibrose canalicular), fotofobia; distúrbios oculomotores e neurite óptica. (SHARMA; GUPTA; VERMA, 2019; BUKHARI; ALESSA; BEHEIRI, 2018;EUROFARMA, 2015;GREM, 2000;SHAPIRO et al, 1985;SUN;HUA, 2019) Em relação à toxicidade dermatológica, são evidenciados na literatura casos de erupção cutânea (enxantema), fotossensibilidade, eritrodisestesia palmo-plantar (síndrome mão-pé), alopecia, dermatite, hiperpigmentação, hipopigmentação, urticaria, ressecamento da pele, fissuração, erosão, avermelhamento de queratoses acrínicas, urticária, onicólise e infecções bacterianas secundárias.…”
Section: Efeitos Colaterais Do 5-fuunclassified